Pengaruh Disiplin Kerja, Lingkungan Kerja, dan Insentif Terhadap Prestasi Kerja Karyawan STIKes di Yogyakarta - Shinta Noriyah; Eplisandri Setyarini; Eko Yulianto (SMARTINDO, 2025)
Employee performance is a key factor in the success of a company. Optimal performance can be achieved through various factors, including work discipline, work environment, and work incentives. Work discipline plays a role in maintaining order and employee responsibility for the tasks assigned. A comfortable work environment can increase employee motivation and productivity. Meanwhile, work incentives can motivate employees to work better. These three factors are interrelated and can influence an individual's work performance within an organization. This study aims to analyze the influence of work discipline, work environment, and incentives on employee performance at STIKes Yogyakarta. This study uses a survey method by distributing questionnaires to employees and educational staff. The data analysis techniques used are multiple linear regression, T-test (partial), F-test (simultaneous), and the coefficient of determination to determine the magnitude of the influence of each independent variable on the dependent variable. The results of the study indicate that work discipline does not significantly influence human resource performance, the work environment significantly influences employee performance, and incentives significantly influence employee performance. The recommendation from this study is that the management of STIKes Yogyakarta needs to continue developing policies that support these three aspects to improve performance quality sustainably.